Withdrawal of Antiepileptic Drugs Following Surgical Treatment of Drug-Resistant Epilepsy - Irina G. Areshkina; Yuri V. Mozheiko; Anna A. Usoltseva; Nikita P. Utyashev; Violetta D. Poleshchuk; Diana V. Dmitrenko (Анналы клинической и экспериментальной неврологии)
The number of patients with successful outcomes following surgical treatment of drug-resistant epilepsy has been rapidly increasing. This trend has heightened the relevance of addressing the appropriateness of postoperative withdrawal of antiepileptic drugs (AED). There are no unified guidelines regarding the optimal timing and rates for discontinuing pharmacological therapy. This article reviews the timing, rate, and specifics of AED withdrawal following surgical treatment of drug-resistant epilepsy using two exemplary clinical cases. The decision to discontinue pharmacotherapy depends on multiple factors, including patient preferences. In cases of favorable outcomes following epilepsy surgery, AED withdrawal one year into remission is considered safe and does not affect long-term seizure outcomes in adult patients who have undergone anterior temporal lobectomy, remain completely seizure- and aura-free, and show no epileptiform activity on electroencephalography. Patients with multiple epileptogenic zones, epileptiform EEG activity, or persistent seizures/auras have less favorable prognoses regarding AED withdrawal.